Realization of high capacity transmission in fiber optic communication systems using absolute polar duty cycle division multiplexing (AP-DCDM) technique - Malekmohammadi, A.; Mahdiraji, G.A.; Abas, A.F.; Abdullah, M.K.; Mokhtar, M.; Rasid, M.F.A. (Optical Fiber Technology, 2009)
An electrical multiplexing technique, namely Absolute Polar Duty Cycle Division Multiplexing (AP-DCDM) is reported for high-speed optical fiber communication systems. It is demonstrated that 40 Gb/s (4 x 10 Gb/s) AP-DCDM system shows a clear advantage over conventional 40 Gb/s RZ-OOK with 50 duty cycle in terms of dispersion tolerance and spectral efficiency. At 40 Gb/s its tolerance to chromatic dispersion (CD) is 124 ps/nm and 194 ps/nm for the worst and the best user, respectively. These values are higher than that of 40 Gb/s RZ-OOK, which is around 100 ps/nm. The spectral efficiency, receiver sensitivity and OSNR for different number of channels are discussed. Comparison against other modulation formats namely duobinary, Non-Return-to-Zero (NRZ)-OOK and RZ-Differential Quadrature Phase-Shift Keying (RZ-DQPSK) at 40 Gb/s are made. It is shown that AP-DCDM has the best receiver sensitivity (-32 dBm) and better CD tolerance (+/- 200 ps/nm) than NRZ-OOK and RZ-DQPSK. In reference to duobinary, AP-DCDM has better receiver sensitivity but worse dispersion tolerance.